The Row House in Washington, DC : A History - Hoagland, Alison K., 1951- (Book collections on Project MUSE., 2023)
"Delving into one of the most intimate aspects of people's lives-their home-and placing it in the larger context of historical forces, this book shows row houses to be both personal and public. The row house was the most popular form of housing in Washington, and its examination reveals it to be a rich environment for understanding change-social, racial, technological, economic, and stylistic"--